ABC of clinical leadership - Swanwick, Tim; McKimm, Judy; Swanwick, Tim (Hoboken, NJ : Wiley-Blackwell, 2017)
The ABC of Clinical Leadership explores and develops the key principles of leadership and management. It outlines the scope of clinical leadership, emphasising its importance in the clinical context, especially for improving patient care and health outcomes in rapidly changing health systems and organisations. Using short illustrative case studies, the book takes a systematic approach to leadership of clinical services, systems and organisations; working with others and developing individual leadership skills. This second edition has been fully updated to reflect recent developments in the field, including current thinking in leadership theory, as well as a focus throughout on workforce development and working in multidisciplinary healthcare teams. International examples are used to reflect global practice and two new chapters on leading projects and followership have been added. Combining theory and practical clinical examples, and written by clinical educators with a wealth of experience of leadership in the clinical and educational environment, the ABC of Clinical Leadership is an ideal resource for all healthcare professionals, both during training and for continuing professional development--Provided by publisher.
Includes bibliographical references and index.
Keywords: Clinical Medicine; Leadership; Physician Executives